The Effect of Heat Treatment on The Hardness and Impact Properties of Medium Carbon Steel - Nurul Aida, Amir Khatif; Mohamad Aliff Kamil, Awang Kecik; Mohd Ali Hanafiah, Shaharudin; A. K., Prasada Rao; Noor Mazni, Ismail (2015)
This paper covers the effect of heat treatment on the mechanical properties of medium carbon steel. The main objective of this project is to investigate the hardness and impact properties of medium carbon steel treated at different heat treatment processes. Three types of heat treatment were performed in this project which are annealing, quenching and tempering. During annealing process, the specimens were heated at 900oC and soaked for 1 hour in the furnace. The specimens were then quenched in a medium of water and open air, respectively. The treatment was followed by tempering processes which were done at 300oC, 450oC, and 600oC with a soaking time of 2 hours for each temperature. After the heat treatment process completed, Rockwell hardness test and Charpy impact test were performed. The results collected from the Rockwell hardness test and Charpy impact test on the samples after quenching and tempering were compared and analysed. The fractured surfaces of the samples were also been examined by using Scanning Electron Microscope. It was observed that different heat treatment processes gave different hardness value and impact property to the steel. The specimen with the highest hardness was found in samples quenched in water. Besides, the microstructure obtained after tempering provided a good combination of mechanical properties due to the process reduce brittleness by increasing ductility and toughness